2018
DOI: 10.4274/balkanmedj.2017.1406
|View full text |Cite
|
Sign up to set email alerts
|

Association of Tryptophan Hydroxylase-2 Gene rs4290270 with Primary Insomnia and Depressive Symptoms in a Chinese Han Population

Abstract: Background:Insomnia often coexists with depression, and there is compelling evidence for a genetic component in the etiologies of both disorders.Aims:To investigate the relationship between exonic variant (rs4290270) in the tryptophan hydroxylase-2 gene and primary insomnia and symptoms of depression in Han Chinese.Study Design:Case-control study.Methods:This study included 152 patients with primary insomnia and 164 age- and gender-matched normal controls. All patients were investigated by polysomnography for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…rs4290270 was prominently associated to the early wakening MDD group rather than the whole MDD group and non-early wakening MDD group. This result was consistent with a previous study which reported that rs4290270 served as a biomarker for depression patients with primary insomnia in Han Chinese population ( Mei et al, 2018 ). In the past, rs4290270 showed an association between symptoms of disturbed sleep and MDD ( Utge, 2012 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…rs4290270 was prominently associated to the early wakening MDD group rather than the whole MDD group and non-early wakening MDD group. This result was consistent with a previous study which reported that rs4290270 served as a biomarker for depression patients with primary insomnia in Han Chinese population ( Mei et al, 2018 ). In the past, rs4290270 showed an association between symptoms of disturbed sleep and MDD ( Utge, 2012 ).…”
Section: Discussionsupporting
confidence: 93%
“…TPH-2 has been widely debated as a major candidate gene in numerous psychiatric disorders including MDD, anxiety, schizophrenia, and bipolar disorder ( Zill et al, 2004 ). Numerous candidate TPH-2 variants, namely rs4290270 ( Shen et al, 2011 ; Wang et al, 2015 ; Karanovic et al, 2017 ; Mei et al, 2018 ), rs4570625 ( Gao et al, 2012 ; Mandelli et al, 2012 ; Lehto et al, 2015 ; Han et al, 2017 ; Piel et al, 2018 ; Wigner et al, 2018 ), rs41317118 ( Xu et al, 2013 ), rs11178998 ( Xu et al, 2016 ; Ottenhof et al, 2018 ), rs7305115 ( Ke et al, 2006 ; Van der Auwera et al, 2014 ; Wang et al, 2015 ; Ottenhof et al, 2018 ), rs17110747 ( Tsai et al, 2009 ; Ottenhof et al, 2018 ), rs10748185 ( Serretti et al, 2011 ; Ottenhof et al, 2018 ), rs18438099 ( Anttila et al, 2009 ; Ottenhof et al, 2018 ), rs11316791, rs1386493, rs1386494 ( Haghighi et al, 2008 ), have been prominently associated with MDD. The exonal variants, rs7305115 and rs4290270, were prominently associated with MDD and disturbed sleep ( Utge, 2012 ; Mei et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the 5-HT system was found to participate in the regulation of sleep and wake statues. 26 1,[28][29][30] However, these risk factors cannot fully predict the risk for insomnia. An increasing number of genes and variants have been examined as promising candidate risk factors for insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…Data were excluded in cases of a normal sleeping state affected by accommodation condition. The following polysomnography indexes were assessed: (i) sleep efficiency; (ii) total sleep time; (iii) sleep latency; (iv) arousal index; (v) percentage of stage 1 (S1%), stage 2 (S2%), stage 3 (S3%) and stage 4 (S4%): the proportion of stage 1, stage 2, stage 3 and stage 4, respectively, to the total sleep time 1,22 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation